2020
DOI: 10.2147/opth.s239103
|View full text |Cite
|
Sign up to set email alerts
|

<p>Refractive Outcomes After Trabecular Micro-Bypass Stents (iStent <em>Inject</em>) with Cataract Extraction in Open-Angle Glaucoma</p>

Abstract: Purpose: Simultaneous cataract and glaucoma surgery has traditionally been challenging for the anterior segment surgeon. The introduction of minimally invasive glaucoma surgery (MIGS) in conjunction with cataract surgery appears safe and effective in lowering intraocular pressure. Although a significant visual impact leading from the combined procedure is unexpected, we aim to describe the refractive outcomes in a cohort of patients undergoing simultaneous cataract removal and iStent inject and discuss the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…18 Also, in 2020 a study result that iStent inject does not risk refractive outcomes and can be paired with cataract procedure safely. 19 In addition, most patients reported that there were no changes in their occupational, social and economic status following MIGS (85.2%, 59.8% and 98.8%) respectively. Since most of patients were over 60 years of age and retired, this may explain why their occupational life did not change and their economic status was not affected by changes in increased or decreased number of eye drops, as our institution provides free eye drops to all patients.…”
Section: Discussionmentioning
confidence: 95%
“…18 Also, in 2020 a study result that iStent inject does not risk refractive outcomes and can be paired with cataract procedure safely. 19 In addition, most patients reported that there were no changes in their occupational, social and economic status following MIGS (85.2%, 59.8% and 98.8%) respectively. Since most of patients were over 60 years of age and retired, this may explain why their occupational life did not change and their economic status was not affected by changes in increased or decreased number of eye drops, as our institution provides free eye drops to all patients.…”
Section: Discussionmentioning
confidence: 95%
“…In summary, the results from previous studies and the present study demonstrated a significant reduction in medication use, and a significant proportion of patients ceased their medication after combination procedures [ 12 , 13 , 18 ]. These results are valuable in the context of disease progression, quality of life, secondary ocular surface disease, medication costs, and psychological aspects [ 9 , 10 , 15 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scott et al reported 80% and 95% of eyes within 0.50 D and 1.00 D, respectively, after iStent® implant and cataract surgery [ 9 ]. Recently, Ioannidis et al reported that 73.8% of eyes had SEs ≤ 0.50 D and 98.9% of eyes had SEs ≤ 1.00 D [ 23 ]. The National Health Service data suggested a benchmark standard of 55% within 0.50 D and 85% within 1.00 D; 62.3% of patients within 0.50 D of the refractive target should represent a minimum level of efficiency following cataract surgery [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been studied extensively and are established as a safe and effective option in various types of OAG with and without concomitant cataract surgery. 7 40 However, relatively few studies have been completed in Japanese patients 11 , 23 or in NTG. 24 , 25 …”
Section: Introductionmentioning
confidence: 99%